MicroRNA-455-3p as a Potential Biomarker for Alzheimer's Disease: An Update - Kumar, Subodh; Reddy, P. Hemachandra (Frontiers in Aging Neuroscience, 2018)
A non-invasive and early-detectable peripheral biomarker is urgently needed for Alzheimer’s disease (AD). The present study is a step forward to verify the biomarker properties of human microRNA-455-3p (Hsa-miR-455-3p) in AD patients. Our previous findings on mild cognitive impaired subjects, AD patients and AD cells and mouse models unveiled the miR-455-3p as a potential peripheral biomarker for AD. In the current study, we verified the differential expression of miR-455-3p in postmortem AD brains obtained from NIH NeuroBioBank, and fibroblasts and B-lymphocytes from both familial and sporadic AD patients from Coriell Cell Repository of National Institutes on Aging. Total RNA was extracted from the fibroblasts, B-lymphocytes and AD postmortem brains, and expression of miR-455-3p was measured by real-time reverse-transcriptase RT-PCR. Our real-time RT-PCR analysis showed a significant (P=0.0002) upregulation of miR-455-3p expression in AD postmortem brains compared to healthy control samples. Expression of miR-455-3p was also upregulated in the fibroblasts from AD patients, however a significant difference in miR-455-3p level was observed in the cells from sporadic AD patients (P=0.014) compared to healthy controls. Similarly, in B-lymphocytes, miR-455-3p level was also higher (P=0.044) especially in sporadic AD cases compared to controls. Receiver operating characteristic (ROC) curve analysis indicated the significant area under ROC curve (AUROC) value of miR-455-3p in AD postmortem brain (AUROC=0.792; P=0.001) and AD fibroblasts cells (AUROC=0.861; P=0.03), whereas in B-lymphocytes AUROC value of miR-455-3p was not significant. Further, in-silico analysis for miRNA targets predictions showed the binding capacity of miR-455-3p with several AD associated key genes such as APP, NGF, USP25, PDRG1, SMAD4, UBQLN1, SMAD2, TP73, VAMP2, HSPBAP1 and NRXN1. Hence, these observations further revealed that miR-455-3p is a potential biomarker for AD and its possible therapeutic target for AD.